Association between exercise and clinical outcomes in patients treated with immunotherapy for solid tumors - Loo, Kimberly; Lavery, Jessica A.; Palmer, Jessica; Guo, Winston; Underwood, Whitney P.; Moskowitz, Chaya S.; Jones, Lee W.; Betof, Allison S. (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICI) have revolutionized the treatment of advanced cancers, but overall response rates remain modest and adjunct therapies to enhance efficacy of ICI are of great interest. This retrospective study examines the association between exercise and clinical outcomes in 258 patients with advanced solid tumors receiving ICI. The results suggest an association between exercise and better clinical outcomes, particularly in patients with high tumor mutation burden, though improvements in clinical benefit rate (58% vs. 51% for exercisers and non-exercisers, respectively) and one-year overall survival (67% vs. 58% for exercisers and non-exercisers, respectively) are not statistically significant. Our discovery-based findings in conjunction with preclinical evidence create a strong rationale for translational studies to formally investigate the effects of structured exercise therapy in combination with ICI in patients with solid tumors.